Levodopa-Induced Dyskinesia in Parkinson Disease Specifically Associates With Dopaminergic Depletion in Sensorimotor-Related Functional Subregions of the Striatum. (June 2021) - Labrador-Espinosa, Miguel A.; Grothe, Michel J.; Macías-García, Daniel; Jesús, Silvia; Adarmes-Gómez, Astrid; Muñoz-Delgado, Laura; Fernández-Rodríguez, Paula; Martín-Rodríguez, Juan Francisco; Huertas, Ismael; García-Solís, David; Mir, Pablo
Abstract : Purpose: To determine whether the development of levodopa-induced dyskinesia (LID) in Parkinson disease (PD) specifically relates to dopaminergic depletion in sensorimotor-related subregions of the striatum. Methods: Our primary study sample consisted of 185 locally recruited PD patients, of which 73 (40%) developed LID. Retrospective 123 I-FP-CIT SPECT data were used to quantify the specific dopamine transporter (DAT) binding ratio within distinct functionally defined striatal subregions related to limbic, executive, and sensorimotor systems. Regional DAT levels were contrasted between patients who developed LID (PD + LID) and those who did not (PD-LID) using analysis of covariance models controlled for demographic and clinical features. For validation of the findings and assessment of the evolution of LID-associated DAT changes from an early disease stage, we also studied serial 123 I-FP-CIT SPECT data from 343 de novo PD patients enrolled in the Parkinson Progression Marker's Initiative using mixed linear model analysis. Results: Compared with PD-LID, DAT level reductions in PD + LID patients were most pronounced in the sensorimotor striatal subregion ( F = 5.99, P = 0.016) and also significant in the executive-related subregion ( F = 5.30, P = 0.023). In the Parkinson Progression Marker's Initiative cohort, DAT levels in PD + LID (n = 161, 47%) were only significantly reduced compared with PD-LID in the sensorimotor striatal subregion ( t = −2.05, P = 0.041), and this difference was already present at baseline and remained largely constant over time. Conclusion: Measuring DAT depletion in functionally defined sensorimotor-related striatal regions of interest may provide a more sensitive tool to detect LID-associated dopaminergic changes at an early disease stage and could improve individual prognosis of this common clinical complication in PD. Abstract : Supplemental digital content is available in the text.